Muzeum zorientowane na odbiorcę. Strategie edukacyjne budujące długookresowe relacje z widzem jako usługobiorcą - Rogozińska, Anna (Studia Edukacyjne, 2020)
This article discusses the role of marketing in the transformation of a museum. The museum should become a service organization with a diverse range of activities, concentred on the audience. There is a real chance that the introduction of relationship marketing in the museum will help it fulfil its mission. Relationship marketing treated as an approach which permeates the all institutional structures and helps to manage the whole museum: it is both the manager path, as well as all museum staff. This marketing is focused not only on promotion and communication, but is also used in shaping the museum educational strategies and planning further institutional activities. From this perspective, marketing is an orientation and a set of specialized practices, it has become a way to understand common values and to achieve specific goals.